2018
DOI: 10.26858/jptp.v2i2.5165
|View full text |Cite
|
Sign up to set email alerts
|

PENGEMBANGAN PRODUK SOSIS FUNGSIONAL BERBAHAN DASAR IKAN TENGGIRI (Scomberomorus sp.) DAN TEPUNG DAUN KELOR (Moringa oleifera L)

Abstract: The purpose of this research is to know the nutrition of the fish sausage and the acceptation of the panellist of the functional fish sausage. This research was done by two steps which the first step is hedonic test and the second step is chemistry analysis. The data analysis used Completely Randomized Design and analysis of variances (ANOVA) which was tested with least significant different test (BNT) in 5% extent. The Result of research shows that the best of water levels treatment of A3B1 (600gr of fish mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
17

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 0 publications
1
2
0
17
Order By: Relevance
“…On the other hand, this can also be caused by M. oleifera leaves which contain fiber, which is in the range of 7.92 g/100 g, so that the addition of M. oleifera leaves reduces the level of elasticity of the resulting nugget texture. This result is in agreement with Nurlaila et al (2018), which reported that increasing the moringa flour in the mackerel sausage,increases the hardness and reduces the springiness. Overall acceptance of panelists showed that the most preferred nuggets are the fish nuggets without the addition of M. oleifera leaves in terms of color, taste, flavor, and texture.…”
Section: Sensory Characteristicssupporting
confidence: 93%
“…On the other hand, this can also be caused by M. oleifera leaves which contain fiber, which is in the range of 7.92 g/100 g, so that the addition of M. oleifera leaves reduces the level of elasticity of the resulting nugget texture. This result is in agreement with Nurlaila et al (2018), which reported that increasing the moringa flour in the mackerel sausage,increases the hardness and reduces the springiness. Overall acceptance of panelists showed that the most preferred nuggets are the fish nuggets without the addition of M. oleifera leaves in terms of color, taste, flavor, and texture.…”
Section: Sensory Characteristicssupporting
confidence: 93%
“…Semakin banyak penambahan tepung daun kelor warna yang dihasilkan produk menjadi warna hijau hingga hijau tua (Hasanah Hafidhah, 2015dalam Nurlaila et al, 2018. Sesuai dengan penelitian yang dilakukan oleh Nurlaila et al, (2018) dalam pembuatan sosis fungsional berbahan dasar ikan tenggiri dan tepung daun kelor.…”
Section: Pembahasanunclassified
“…Ada empat jenis rasa dasar yang dikenali oleh manusia yaitu asin, asam, manis dan pahit (Hasniar et al, 2019).. Rasa suatu bahan makanan merupakan faktor yang menentukan apakah produk tersebut disukai atau tidak oleh konsumen. Rasa suatu bahan makanan merupakan hasil kerjasama indera-indera lain, seperti indera penglihatan, pembauan, pendengaran, dan perabaan (Nurlaila et al, 2016). Hasil hedonik terhadap rasa siomay krokot yang dilakukan oleh 25 orang panelis semi terlatih dapat dilihat pada Gambar 4.…”
Section: D) Rasaunclassified